Exploring moral distress in pediatric oncology; a sample of registered practitioners. (December 2013) - Pye, Kate
<x xml:space="preserve">Abstract</x> The aim of this research was to explore perceptions of doctors and nurses working in an English regional pediatric oncology unit, regarding their lived experiences and feelings relating to the concept of moral distress. This was undertaken to illuminate the understanding of team dynamics and the impact that the causes and repercussions of moral distress may have on that team. The qualitative methodology was influenced by the Heideggarian phenomenological approach and data analysis was undertaken using Colaizzi's (1978) phenomenological method for protocol analysis. Six main themes were identified expressing participants' experiences of morally distressing situations, with three warranting in depth exploration: "the importance of the decision-making processes, " "conflict over right to treatment and withholding treatment, " and "communication within the team." Moral distress does occur within pediatric oncology clinical settings and it has unavoidable triggers including emotional responses to difficult scenarios. The implications of this small study show benefits in sharing the decision-making process, thus enabling staff to recognize triggers more efficiently in clinical practice, enhancing communication through training and further research, collaborative education, de-briefing, and team meetings.